ITEM ANALYSIS AND INTERNAL CONSISTENCY OF CHILDREN’S SLEEP HABIT QUESTIONNAIRE (CSHQ) IN INDONESIAN VERSION - Sri Hartini; Sunartini Sunartini; Elsisabeth Siti Herini; Satoshi Takada (Belitung Raya Foundation, Indonesia, 2017)
Background: The Children’s Sleep Habit Questionnaire (CSHQ) has been utilized for assessing sleep behavior problems in children aged 4-10 years in many countries. However, a proper tool to detect of sleep behavior problems in Indonesian children has not been proven. Aims: The aim of our study was to test the item analysis and internal consistency of the Children’s Sleep Habit Questionnaire (CSHQ) in Indonesian version. Methods: We used a cross-sectional design and 305 mothers of pre- and primary school children in Yogyakarta Indonesia participated in this study. The Indonesian version of the Children’s Sleep Habit Questionnaire was used for assessing the sleep behavior problems in children. Internal consistency was evaluated by using the Cronbach α method. The internal consistency was tested with Cronbach alpha coefficients. Pearson’s Product Moment was completed to estimate the correlation between all items of CSHQ with Subscales and total scores of CSHQ. Results: Internal consistency of all items of the Children’s Sleep Habit Questionnaire was 0.80. Internal consistency of subscales ranged from 0.42 (parasomnias) to 0.66 (night wakening). 31 of 33 items had significant positive correlation with total score of Children’s Sleep Habit Questionnaire. Inter-subscales with the highest correlation were sleep onset delay with parasomnias, parasomnias with sleeps disordered breathing, and sleep disorder breathing with night waking. Conclusions: The Indonesian version of the Children’s Sleep Habit Questionnaire is suitable for screening sleep behavior problems in Indonesian children aged 4-10 years.